ANALISIS DAMPAK PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT FIFGROUP CABANG LAMPUNG - Atmaja, I Wayan Eka Sura (Jurnal Manajemen Magister Darmajaya, 2017)
Every company or organization certainly wants to live long and keeps growing. To be able to live and grow well, a company is demanded to pay attention to human resource aspects existing in the organization, including job training and work motivation to the employees. This research was conducted at PT FIFGROUP Lampung Branch. The objective of the study was to know the impacts of job training and work motivation on the employee performance at PT FIFGROUP Lampung Branch both partially and simultaneously.It was a quantitative research using census method. The population in the study was all permanent employees of PT FIFGROUP Lampung Branch as 112 employees. The data of the research was collected by using interview, questionnaire, observation, and library research. The data analysis technique used in this research was multiple regression analysis, t-test and F-test assisted with SPSS application in processing the data. The result shows that this research accepts the hypothesis that is the job training and work motivation have a positive and significant impact on employee performance at PT FIFGROUP Lampung Branch either partially and simultaneously. To achieve a better performance, it is suggested to the company to pay attention to cost effectiveness aspects in conducting job training program, improving working hours in the organization and paying attention to job quality of the employees.  Keywords:       Job Training, Work Motivation, Performance